Attitudes towards protection of biodiversity in forests : a case study of forest owners in Skåne, Sweden - Hedwall, Per-Ola (SLU/Southern Swedish Forest Research Centre, 2004)
The focus of nature protection through area protection in Swedish forests has for a long time been on boreal, subalpine and alpine areas. Large areas have of this reason been protected in northern Sweden, while the protection of forest in southern Sweden, and especially in the temperate zone, have been almost neglected. Only 2,5 per cent of the land area in the southernmost county in Sweden, the county of Skåne, has some kind of protection today and considerably less of the forest is protected. Some possible reasons for this distorted balance of share of protected forest between northern and southern Sweden are: